STUDENTS’ ATTITUDE TO PHYSICAL ACTIVITY UNDER BLENDED LEARNING - Glazkova, G.B.; Lubyshev, E.A.; Mamonova, O.V.; Pukhovskaya, M.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the attitude of students to physical activity during the period of COVID-19 (2019-2022). Methods and structure of the study. The empirical study (Internet survey), which took place during three years of study (1-3 courses), was attended by students of the Plekhanov Russian University of Economics (n=1272). Results and conclusions. The survey showed a decrease in the physical activity of students, a slight increase in the number of young people who do not go in for physical exercises. Among the students involved in motor activities, there was a more rational distribution of time with devices: 2-3 hours - (8.6-14.7-13.9%), 4-6 hours - (36.4-41.9-41.9%), positive changes in the frequency of classes per week (every day (32.85-22.7-29.1%); 2-3 times a week (40.6-49.8-44.7%); increasing the use of individual complexes for the prevention of posture disorders (8.1-11.2-13.6%) The findings of the study allowed us to develop an experimental method of physical education in a mixed learning format.